Investigating the production and synergistic antibacterial activity of bacteriocin-like substance from Brevibacillus laterosporus SA-14 (TISTR 2453) for enhanced wound healing - Husna Madoromae; Apichart Atipairin; Malatee Tayeh; Monthon Lertcanawanichakul (Heliyon)
The rise in antimicrobial-resistant (AMR) bacteria, especially Methicillin-resistant Staphylococcus aureus (MRSA), is a global health concern. Bacteriocins are promising antibiotic alternatives. This study aimed to enhance the production of bacteriocin-like substances (BLS) from Brevibacillus laterosporus SA-14 (TISTR 2453) by optimizing nutrients, evaluating antibacterial activity, assessing synergy with vancomycin, and testing the cytotoxicity and wound healing effects on human keratinocytes. The results showed that when the SA-14 strain was cultured in half-formula Luria-Bertani broth (LB/2) with added carbon sources (glucose, sucrose, and lactose), all cultures reached the late log phase at 24 h, and antibacterial activity was exhibited against various MRSA strains after 48 h, except for the LB/2 supplemented with glucose, likely due to carbon catabolite repression. However, the addition of nitrogen sources, including skim milk, peptone, and beef extract resulted in high antibacterial activity at 48 h, with skim milk being the most effective for BLS production. The BLS was precipitated with 80 % ammonium sulfate, achieving a 38.09 % yield and a protein concentration of 6.97 ± 1.12 mg/mL. The SDS-PAGE analysis revealed five bands of proteins with molecular weights of 25–250 kDa. The minimum inhibitory concentration of BLS ranged from 0.44 to 0.87 mg/mL, with an minimum bactericidal concentration) of 0.87 mg/mL for all MRSA strains. A synergistic effect with vancomycin was observed at 0.22 mg/mL BLS and 1 μg/mL vancomycin, with an fractional inhibitory concentration index of 1.00, indicating an additive effect. At a concentration of 0.22 mg/mL, BLS was non-cytotoxic to HaCaT cells and promoted complete wound healing after 48 h. Therefore, BLS produced by the SA-14 strain is suitable for controlling AMR, especially MRSA, and has the potential for application in wound dressings in the future.